KAJIAN YURIDIS HAK LANGGEH (SYUF’AH) DALAM ADAT MASYARAKAT ACEH DI KOTA LANGSA - AULIA RAHMAN (PREMISE LAW JURNAL, 2015)
The civil law in Aceh mostly regulates various kinds of way of life in communities, nationality, and with a state. One of the regulations in the civil law is about muamalah (social life), especially about hak langgeh (syuf’ah). It is a requirement which has to be fulfilled before a person/legal entity performs a transaction of buy and sell land besides the rewgulation stipulated in the Government Regulation No. 24/1997 on Land registration. It is because hak langgeh (syuf’ah) has existed and developed in Aceh adat law. In practice, however, many people in Langsa ignore the norm of hak langgeh (syuf’ah); in consequence, there are many disputes in the case of buy and sell land which causes the loss for the seller, the buyer, and PPAT (official empowered to draw up deeds). The problems of the research were as follows: how about the existence of hak langgeh (syuf’ah) in Aceh community in Langsa, how about the settlement of dispute in hak langgeh (syuf’ah in Aceh community in Langsa, and how effective the settlement of the dispute in hak langgeh (syuf’ah) by adat law in Aceh community in Langsa. Keywords: Hak Langgeh (Syuf’ah), Adat, Aceh